QR CODE–ENABLED DIGITAL BADMINTON MODULES IN HIGHER PHYSICAL EDUCATION: DEVELOPMENT, USABILITY, LEARNING AUTONOMY, AND MOTOR SKILL OUTCOMES - Rohmad; Wanuh Wiyarko (CV. TOTUS TUUS, 2026)
Practice-oriented badminton courses require students to translate technical explanations into rapid, coordinated movement, yet conventional printed modules cannot adequately represent temporal, spatial, and biomechanical features of strokes. This study developed and evaluated a QR code–enabled digital badminton module designed as an on-court visual learning assistant for physical education students. A research-and-development design using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model involved 55 purposively selected students: 15 in a small-scale trial and 40 in a large-scale trial. Data were collected through content- and media-expert validation forms, student-response questionnaires, and observational motor-skill assessments. Expert validation indicated very high feasibility for content (88.00%), language and theoretical presentation (86.00%), graphic design (92.00%), and QR functionality (94.00%). In the large-scale trial, positive responses reached 90.50% for access ease, 88.20% for video clarity, 86.80% for independent practice, and 92.00% for learning motivation. Reported pre–post comparisons showed significant improvements in short serve (gain = 16.30, p = .002), clear lob (gain = 23.20, p = .001), and drop shot performance (gain = 19.50, p = .004). The findings indicate that a low-friction combination of concise printed guidance, cloud-hosted video, and instant QR access can support independent rehearsal and motor-skill learning in higher physical education. The study contributes a field-oriented hybrid-media design that minimizes navigation demands during physical practice. Future research should use multisite controlled trials, report effect sizes and retention outcomes, and test offline access and automated motion-feedback features.